Determinants of Perceived Effectiveness of Organic Fertilizer Used by Farmers in Oyo State, Nigeria - Oluwasegun Fasina Oluwatosin (Agricultura Tropica et Subtropica, 2013)
The study examined the determinants of the perceived effectiveness of an organic fertilizer used by farmers in Oyo state, Nigeria. A stratified and purposive sampling technique was used to select 110 respondents from three major vegetation zones of the study area. Descriptive statistics were used to present the findings of the study while the Chi-square analysis was used to test the study hypotheses. Data revealed that 77.3% were aware of the organic fertilizer while only 60.0% of those aware made use of the fertilizer. Among the users, 37.3% applied 25 g of the organic fertilizer per crop stand which was largely on maize (92.16%). Average rate of application was 0.40 tons per hectare. Application method was mainly through side dressing (58.82%) and ‘dig and cover’ (29.41%). Time of application varied from the time of sowing to 4 weeks after planting with the majority of farmers (64.71%) applying at 2 weeks after planting. Interest in the continuous use of the fertilizer was high (62.75%) and the majority of users (52.95%) perceived that the organic fertilizer was effective. Chi-square analysis revealed that the rate and method of application were significantly related to the effectiveness of the fertilizer (χ2 = 15.66, P < 0.05 and χ2 = 8.79, P < 0.05, respectively). Rate and method of application are thus significant determinants to fertilizer effectiveness. Extension activity should therefore focus on farmer education to ensure proper use of the organic fertilizer for maximum productivity